2019
DOI: 10.1039/c9ra09235h
|View full text |Cite
|
Sign up to set email alerts
|

Novel stereoselective syntheses of N-octyl-β-valienamine (NOV) and N-octyl-4-epi-β-valienamine (NOEV) from (−)-shikimic acid

Abstract: Novel stereoselective syntheses of N-octyl-β-valienamine (NOV) 1 and N-octyl-4-epi-β-valienamine (NOEV) 2 starting from naturally abundant (−)-shikimic acid are described in this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Recently, Li et al 91 ) reported an efficient synthesis of 26 and 27 from naturally abundant shikimic acid with overall yields of 31% (14 steps) and 19% (17 steps), respectively.…”
Section: Development Of Carbaglycosylamine-based Pharmacological Chap...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Li et al 91 ) reported an efficient synthesis of 26 and 27 from naturally abundant shikimic acid with overall yields of 31% (14 steps) and 19% (17 steps), respectively.…”
Section: Development Of Carbaglycosylamine-based Pharmacological Chap...mentioning
confidence: 99%
“…Debenzoylation of the mixture in basic conditions led to the formation of the ,bromide 166 and the ,-epoxide 167 in 47% and 26% yield, respectively. Because the subsequent coupling reaction of 166 and 167 with n-octylamine yielded the same product,89) the mixture of 166 and 167, without isolation, was treated with n-octylamine followed by deisopropylidenation to give 27 as the sole product in 47% yield.Recently, Li et al91) reported an efficient synthesis of 26 and 27 from naturally abundant shikimic acid with overall yields of 31% (14 steps) and 19% (17 steps), respectively.…”
mentioning
confidence: 99%
“…(−)‐SA 1 is very useful material for syntheses of drugs and pharmaceutically valuable natural products. For examples, it has been extensively used in the syntheses of oseltamivir phosphate (Tamiflu), [7] valiolamine, [8] valienamine, [8a,9] NOV, [10] NOEV, [10] pericosines (A, B, D and E), [11] zeylenones, [12] (−)‐MK7607, [13] previtamin D 3 , [14] quercitols, [15] and (−)‐quinic acid [16] . (−)‐SA 1 and its derivatives might also be very important in drug discovery, since they have shown a wide range of physiological activities [17] such as antiviral, anti‐bacterial, anti‐fungi, anti‐osteoclastogenesis, anti‐platelet, anti‐thrombogenic, anti‐inflammatory, anti‐oxidant, and anti‐tumor activities.…”
Section: Introductionmentioning
confidence: 99%